2023
DOI: 10.1111/cea.14300
|View full text |Cite
|
Sign up to set email alerts
|

Allergic sensitization to foods in India and other Low–Middle‐income countries

Abstract: Food allergy is an important cause of morbidity significantly affecting the quality of life of the sufferer. Food allergy, an important component of the allergy march, may be increasing in prevalence in some regions and constitutes an important public health problem. 1 Awareness of food allergy is increasing in both western as well as developing countries. The burden of challenge-confirmed food allergy in the western world is up to 10%, but is much lower in LMICs.The increasing awareness and prevalence of food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…7 The prevalence of sensitisation to common food allergens was 20% and 25% in children and adults in Karnataka, a southern Indian state, although 'probable allergy' was just about 0.14% and 1.2%, respectively. 7 There are no published data from other Indian states. These data raise some important research questions.…”
Section: Allergy In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…7 The prevalence of sensitisation to common food allergens was 20% and 25% in children and adults in Karnataka, a southern Indian state, although 'probable allergy' was just about 0.14% and 1.2%, respectively. 7 There are no published data from other Indian states. These data raise some important research questions.…”
Section: Allergy In Indiamentioning
confidence: 99%
“…Mahesh et al highlight a very interesting observation made in the EuroPrevall‐INCO study that showed a very high sensitisation rate to food allergens, as evidenced by serum‐specific IgE 7 . The prevalence of sensitisation to common food allergens was 20% and 25% in children and adults in Karnataka, a southern Indian state, although ‘probable allergy’ was just about 0.14% and 1.2%, respectively 7 . There are no published data from other Indian states.…”
Section: Figurementioning
confidence: 99%
“…The incidence of allergic illnesses has risen significantly in the last two to three decades, and it is currently impacting not only developed nations but also underdeveloped/developing economies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Given the unlikelihood of genetic predispositions being the only factor responsible, it is more appropriate to explain this significant rising trend by alterations in environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of allergic diseases has increased dramatically over the past two to three decades, and the second wave of the allergy epidemic is now affecting not only the Western world but also developing countries [1][2][3][4][5][6][7][8][9][10][11][12]. Assuming that modifications in genetic predispositions over such a time frame are unlikely, this dramatic upward trend should rather be attributed to changing environmental factors.…”
Section: Introductionmentioning
confidence: 99%